2014
DOI: 10.1126/science.1254449
|View full text |Cite
|
Sign up to set email alerts
|

Three crocodilian genomes reveal ancestral patterns of evolution among archosaurs

Abstract: To provide context for the diversifications of archosaurs, the group that includes crocodilians, dinosaurs and birds, we generated draft genomes of three crocodilians, Alligator mississippiensis (the American alligator), Crocodylus porosus (the saltwater crocodile), and Gavialis gangeticus (the Indian gharial). We observed an exceptionally slow rate of genome evolution within crocodilians at all levels, including nucleotide substitutions, indels, transposable element content and movement, gene family evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
330
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 320 publications
(359 citation statements)
references
References 176 publications
25
330
1
3
Order By: Relevance
“…In particular, because PSMC is applied to a single diploid genome, it has been used to infer population size histories in numerous species for which one or more genome sequences are available, in many cases finding support for large changes in population size (Groenen et al 2012;Albert et al 2013;Prado-Martinez et al 2013;Zhan et al 2013;Freedman et al 2014;Green et al 2014;Wallberg et al 2014;Auton et al 2015;Lamichhaney et al 2015). Our findings suggest that natural selection may alter the shape of, and inflate the degree of change in, these inferred histories.…”
Section: Discussionmentioning
confidence: 81%
“…In particular, because PSMC is applied to a single diploid genome, it has been used to infer population size histories in numerous species for which one or more genome sequences are available, in many cases finding support for large changes in population size (Groenen et al 2012;Albert et al 2013;Prado-Martinez et al 2013;Zhan et al 2013;Freedman et al 2014;Green et al 2014;Wallberg et al 2014;Auton et al 2015;Lamichhaney et al 2015). Our findings suggest that natural selection may alter the shape of, and inflate the degree of change in, these inferred histories.…”
Section: Discussionmentioning
confidence: 81%
“…Our results also support early (pre-genome) inferences that crocodilian and turtle genomes contained minimal microsatellite landscapes (Shedlock et al 2007). Despite deep divergences among lineages sampled, we found that all crocodilian species contain nearly identical microsatellite landscapes, which further emphasizes the relatively slow rates of molecular evolution in crocodilians -thought to be among the slowest of all vertebrate lineages (Green et al 2014). …”
Section: Divergent Patterns Of Microsatellite Composition In Reptiliamentioning
confidence: 89%
“…They do not constitute a monophyletic group, since some reptiles are more closely related to birds than they are to other reptiles (Green et al, 2014). There are many groups that are now extinct, in some cases due to mass extinction events: pterosaurs, plesiosaurs, ornithischians, sauropods, many theropods, and squamates (e.g., mosasaurids) are examples (Benton, 2014).…”
Section: Reptiles: Unpopular Players In Ecological Processesmentioning
confidence: 99%